A Study on the Application Mechanism of Heart-to-Heart Conversations Conducted by Career-Oriented College Counselors in Ideological and Political Education - Gao, Taixin (Education Insights, 2026)
Against the backdrop of the continuous refinement of the ideological and political education system in universities during the new era, college counselors—acting as the key implementers of student ideological education—play a fundamental and indispensable role in guiding students' thinking, shaping their core values, and correcting their behaviors through dedicated heart-to-heart conversations. Vocational undergraduate education uniquely emphasizes both applied talent cultivation and professional competency enhancement, thereby imposing significantly higher demands for targeted, pragmatic, and highly practical approaches to ideological education. As a highly flexible and personalized educational approach, counselor-led conversations successfully achieve implicit ideological education through deep emotional engagement, proactive psychological counseling, and structured value-oriented guidance. Grounded in the foundational theories of ideological education, interpersonal communication, and modern educational management, this comprehensive study critically analyzes the practical foundations and contemporary challenges of conducting such conversations within vocational undergraduate institutions. Furthermore, it systematically explores their underlying operational mechanisms from a holistic systemic perspective. To address current limitations, this research proposes an innovative operational framework comprising "goal orientation, content stratification, diversified methods, collaborative implementation, and evaluation feedback," alongside actionable optimization strategies. The research ultimately concludes that systematically improving the counseling mechanism substantially enhances the relevance, accessibility, and overall effectiveness of ideological education. This enhancement provides crucial, long-term support for vocational universities in successfully fulfilling their core institutional mission of fostering moral integrity and promoting the holistic development of their student bodies.